2000
DOI: 10.1038/sj.gene.6363680
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the mucosa: genetically engineered vaccines and mucosal immune responses

Abstract: The discovery that inoculation of DNA leads to strong and long lasting immune responses generated enthusiasm to assess the efficacy of various genetically engineered vaccines against mucosally acquired infections. Various techniques have been used to generate the most suitable DNA vaccines, ranging from immunization with naked DNA to utilizing genetically engineered recombinant viruses and bacteria to deliver the DNA. Different DNA vaccine modalities and mucosal immune responses to them have been discussed. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…A recent clinical study has demonstrated that, when BCG was administered mucosally to human volunteers, it preferentially induced a T-cell population expressing mucosal homing molecule ␣4␤7, which was accompanied by reduced purified protein derivative skin reactivity (12). Collectively, our present study supports the notion that airway mucosal immunization provides better immune protection in the lung upon secondary infection (16,22,23,30).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A recent clinical study has demonstrated that, when BCG was administered mucosally to human volunteers, it preferentially induced a T-cell population expressing mucosal homing molecule ␣4␤7, which was accompanied by reduced purified protein derivative skin reactivity (12). Collectively, our present study supports the notion that airway mucosal immunization provides better immune protection in the lung upon secondary infection (16,22,23,30).…”
Section: Discussionsupporting
confidence: 78%
“…Mucosal vaccination has received increasing attention due to its potency in inducing mucosa-associated protection from mucosal infectious diseases (16,23,30). In this regard, both intragastric and intrarectal routes of TB vaccination have been explored, but it was found that not only were larger doses of vaccines required but also the protection level did not exceed that by percutaneous BCG vaccination (1,19).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that cutaneous or intramuscular immunization generates antigen-specific cells that may not travel to mucosal sites (3,11,22,32,49).…”
Section: As Most Human Immunodeficiency Virus (Hiv) Infection Occurs mentioning
confidence: 99%
“…While activated T-cells reenter lymphoid tissues and preferentially accumulate at the site of the initial activation, memory T-cells migrate continuously and randomly, similar to naive T-cells [21] [22]. The implication in terms of HIV infection is that, in the initial phase of an immune response, once primed, Ag-specific memory T-cells randomly enter and leave various lymphoid compartments but preferentially are retained in the lymphoid compartment where the antigen was presented at first [23] [24]. …”
Section: Introductionmentioning
confidence: 99%